Exposures to conditioned flavours with different hedonic values induce contrasted behavioural and brain responses in pigs. - Caroline Clouard (Public Library of Science (PLoS), 2012)
This study investigated the behavioural and brain responses towards conditioned flavours with different hedonic values in juvenile pigs. Twelve 30-kg pigs were given four three-day conditioning sessions: they received three different flavoured meals paired with intraduodenal (i.d.) infusions of 15% glucose (F(Glu)), lithium chloride (F(LiCl)), or saline (control treatment, F(NaCl)). One and five weeks later, the animals were subjected to three two-choice feeding tests without reinforcement to check the acquisition of a conditioned flavour preference or aversion. In between, the anaesthetised pigs were subjected to three (18)FDG PET brain imaging coupled with an olfactogustatory stimulation with the conditioned flavours. During conditioning, the pigs spent more time lying inactive, and investigated their environment less after the F(LiCl) than the F(NaCl) or F(Glu) meals. During the two-choice tests performed one and five weeks later, the F(NaCl) and F(Glu) foods were significantly preferred over the F(LICl) food even in the absence of i.d. infusions. Surprisingly, the F(NaCl) food was also preferred over the F(Glu) food during the first test only, suggesting that, while LiCl i.d. infusions led to a strong flavour aversion, glucose infusions failed to induce flavour preference. As for brain imaging results, exposure to aversive or less preferred flavours triggered global deactivation of the prefrontal cortex, specific activation of the posterior cingulate cortex, as well as asymmetric brain responses in the basal nuclei and the temporal gyrus. In conclusion, postingestive visceral stimuli can modulate the flavour/food hedonism and further feeding choices. Exposure to flavours with different hedonic values induced metabolism differences in neural circuits known to be involved in humans in the characterization of food palatability, feeding motivation, reward expectation, and more generally in the regulation of food intake.